Incidental periprostatic schwannoma discovered during evaluation for prostatic adenocarcinoma - Dietrick, Barbara (Urol Case Rep, 2020)
Schwannomas of the prostate are exceedingly rare. We present a noteworthy case of a sporadic prostatic schwannoma diagnosed in conjunction with prostatic adenocarcinoma. A 60-year-old male presented with mild lower urinary tract symptoms and a prostate specific antigen (PSA) level of 4.84 ng/mL. A transrectal ultrasound guided prostate biopsy revealed multifocal Grade Group 2 prostate cancer. MRI demonstrated a PI-RADS 4 lesion and a periprostatic cystic lesion. Prostatectomy was performed. Final pathology demonstrated prostatic adenocarcinoma, with a separate periprostatic schwannoma. We present the first case in the literature of a sporadic periprostatic schwannoma discovered during evaluation for prostatic adenocarcinoma.